Neural mobilization as a therapeutic option in the treatment of stroke. - Santos, Alan Carlos Nery dos; Goes, Ana Cristina Gusmão de; Lago, Rodrigo Medina Vasconcelos; Petto, Jefferson (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The neural mobilization is a technique aimed at functional recovery of the nervous system and structures innervated by it. However, little is known about its effects in patients affected by stroke (CVA). Objective: To review and integrate studies that investigated the effects of neural mobilization (NM) in the treatment of patients with stroke. Method: an integrative review of scientific studies with primary and secondary data, both addressing the NM in the treatment of spasticity, flexibility and functionality of stroke patients. The review was carried out by independent authors from July to October 2014. databases were consulted: LILACS, PEDRO, PUBMED and SCIELO. For the selection of manuscripts, we used the following key words: Neural Mobilization, Neurodynamics Mobilization, neurodynamic tests, stroke, spasticity Muscle, joint range of motion, flexibility and their counterparts in English. Studies were screened by reading the titles and objectives. Then deleted resumes in duplicate and performed the reading of articles to verify that met the inclusion criteria. Results: Six studies were selected, one being reviewed. In general, all the research has investigated the effects of NM in stroke patients. Four of the six articles were published in English. Only one study used a control group. As for treatment, there was divergence in relation to the NM application protocol. Conclusion: The reviewed studies indicate beneficial effects of neural mobilization in the control of muscle tone, range of motion and functionality of patients affected by stroke.